1998
DOI: 10.1021/ac9804339
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dynamic Liquid-Phase Microextraction to the Analysis of Chlorobenzenes in Water by Using a Conventional Microsyringe

Abstract: A dynamic liquid-phase microextraction technique combined with gas chromatography/mass spectrometry (GC/MS) is described for the extraction of 10 chlorobenzenes from water samples into 1 microL of organic solvent by using a conventional microsyringe. The effects of extraction solvent, plunger movement pattern, sampling volume, number of samplings, and salt concentration on the extraction performance were investigated. Good repeatabilities of extraction were obtained, with the RSD values below 5.3% except for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
110
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(114 citation statements)
references
References 17 publications
3
110
0
1
Order By: Relevance
“…16 Liquid phase microextraction (LPME) is a novel technique and attracts increasing attention due to its merits, which include simplification, low cost, and high enrichment factor. 17,18 Recently, Rezaee, Assadi and coworkers have developed a novel liquid extraction named dispersive liquid-liquid microextraction (DLLME) based on a ternary component solvent system such as homogeneous liquid-liquid extraction and cloud point extraction. 19 The experimental results showed that this microextraction technique exhibited a high performance and powerful enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…16 Liquid phase microextraction (LPME) is a novel technique and attracts increasing attention due to its merits, which include simplification, low cost, and high enrichment factor. 17,18 Recently, Rezaee, Assadi and coworkers have developed a novel liquid extraction named dispersive liquid-liquid microextraction (DLLME) based on a ternary component solvent system such as homogeneous liquid-liquid extraction and cloud point extraction. 19 The experimental results showed that this microextraction technique exhibited a high performance and powerful enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of these compounds is hence important which ensures the safety of human health and properties and also avoids environmental disasters. Numerous methodologies have been demonstrated to determination of chlorobenzenes and nitrobenzoates, such as gas chromatography-mass spectrometry (GC-MS) [2][3][4], high performance liquid chromatography-mass spectrometry (HPLC-MS) [5], sensors [1,6,7] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection of these compounds is hence important which ensures the safety of human health and properties and also avoids environmental disasters. Numerous methodologies have been demonstrated to determination of chlorobenzenes and nitrobenzoates, such as gas chromatography-mass spectrometry (GC-MS) [2][3][4], high performance liquid chromatography-mass spectrometry (HPLC-MS) [5], sensors [1,6,7] etc.Dispersive liquid-liquid microextraction (DLLME) has emerged recently as a new and very efficient alternative technique to concentrate target analytes dissolved in organic extracts, allowing a high enrichment factor in a simple and quick manner [8]. DLLME has been applied for determination of a vast variety of organic and inorganic compounds in different matrices [9,10].…”
mentioning
confidence: 99%
“…An alternative solvent-minimized sample preparation approach to complement SPME appeared in the middle--to-late 1990s [10][11][12]; liquid-phase microextraction (LP-ME) utilizes only a small amount of solvent (low microliter range) for concentrating analytes from aqueous samples. It is simply a miniaturized format of liquid-liquid extraction (LLE) and overcomes many of its disadvantages as well as some of those of SPME (e.g.…”
Section: Introductionmentioning
confidence: 99%